Exercise Training Reduces Inflammation of Adipose Tissue in the Elderly: Cross-Sectional and Randomized Interventional Trial - Čížková, Terezie; Štěpán, Marek; Daďová, Klára; Ondrůjová, Barbora; Sontáková, Lenka; Krauzová, Eva; Matouš, Miloš; Koc, Michal; Gojda, Jan; Kračmerová, Jana; Štich, Vladimír; Rossmeislová, Lenka; et al. (The Journal of clinical endocrinology and metabolism, 2020)
CONTEXT: Metabolic disturbances and a pro-inflammatory state associated with aging and obesity may be mitigated by physical activity or nutrition interventions. OBJECTIVE: The aim of this study is to assess whether physical fitness/exercise training (ET) alleviates inflammation in adipose tissue (AT), particularly in combination with omega-3 supplementation, and whether changes in AT induced by ET can contribute to an improvement of insulin sensitivity and metabolic health in the elderly. DESIGN, PARTICIPANTS, MAIN OUTCOME MEASURES: The effect of physical fitness was determined in cross-sectional comparison of physically active/physically fit (trained) and sedentary/less physically fit (untrained) older women (71 ± 4 years, n = 48); and in double-blind randomized intervention by 4 months of ET with or without omega-3 (Calanus oil) supplementation (n = 55). Physical fitness was evaluated by spiroergometry (maximum graded exercise test) and senior fitness tests. Insulin sensitivity was measured by hyperinsulinemic-euglycemic clamp. Samples of subcutaneous AT were used to analyze mRNA gene expression, cytokine secretion, and immune cell populations. RESULTS: Trained women had lower mRNA levels of inflammation and oxidative stress markers, lower relative content of CD36+ macrophages, and higher relative content of γδT-cells in AT when compared with untrained women. Similar effects were recapitulated in response to a 4-month ET intervention. Content of CD36+ cells, γδT-cells, and mRNA expression of several inflammatory and oxidative stress markers correlated to insulin sensitivity and cardiorespiratory fitness. CONCLUSIONS: In older women, physical fitness is associated with less inflammation in AT. This may contribute to beneficial metabolic outcomes achieved by ET. When combined with ET, omega-3 supplementation had no additional beneficial effects on AT inflammatory characteristics.
Keywords: Insulin Resistance; Cross-Sectional Studies; Aging; Cardiorespiratory Fitness; inzulinová rezistence; kardiorespirační zdatnost; Inflammation; tělesná výkonnost; terapie cvičením; tuková tkáň; cardiorespiratory fitness; adipose tissue inflammation; aging; Aged; insulin sensitivity; senioři; Exercise; svalová síla; zánět; Muscle Strength; senioři nad 80 let; omega-3 fatty acids; lidé; Adipose Tissue; ženské pohlaví; Humans; Exercise Therapy; stárnutí; průřezové studie; Aged, 80 and over; Physical Fitness; Female; cvičení; lidé středního věku; exercise training; Middle Aged